2012
DOI: 10.1097/tp.0b013e318242be28
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Everolimus on Left Ventricular Hypertrophy of De Novo Kidney Transplant Recipients

Abstract: An immunosuppressive regimen consisting of EVL plus reduced exposure CsA proved to be effective in regressing LVH in RTRs regardless of BP, mainly by reducing left ventricular wall thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 27 publications
1
24
2
Order By: Relevance
“…32) Kushwaha, et al showed in HTx recipients that conversion from CNI to SRL decreased LVMI along with increased 14) Little has been reported about the anti-proliferative effect of EVL except for several studies in renal transplant recipients. Paoletti, et al showed in a randomized controlled study that EVL therapy along with reduced CyA was effective in the reduction of LVM among renal transplant recipients, mainly due to reduced LV wall thickness, 34) which was consistent with our results. In contrast, another randomized controlled trial by Murbraech, et al demonstrated that conversion from CyA to EVL had no relevant advantage on the reduction of LVM compared with the non-conversion group in renal transplant recipients.…”
Section: )supporting
confidence: 82%
“…32) Kushwaha, et al showed in HTx recipients that conversion from CNI to SRL decreased LVMI along with increased 14) Little has been reported about the anti-proliferative effect of EVL except for several studies in renal transplant recipients. Paoletti, et al showed in a randomized controlled study that EVL therapy along with reduced CyA was effective in the reduction of LVM among renal transplant recipients, mainly due to reduced LV wall thickness, 34) which was consistent with our results. In contrast, another randomized controlled trial by Murbraech, et al demonstrated that conversion from CyA to EVL had no relevant advantage on the reduction of LVM compared with the non-conversion group in renal transplant recipients.…”
Section: )supporting
confidence: 82%
“…Administration of everolimus, a rapamycin analogue, decreases ventricle hypertrophy in kidney transplant patients. 39 The activation of Akt-mTOR signaling likely contributes to cardiac fibrosis and hypertrophy by enhancing protein synthesis. We provide in vivo evidence of Nox4-derived ROS generation in mTOR activation in the course of cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Paoletti et al demonstrated in controlled studies that both SRL and EVL regress left ventricular mass in KT recipients [6-8]. However, no patient received combined treatment with m-TOR inhibitors and RAS blockers during the first 12 months post-conversion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nonrandomized controlled trials have shown that conversion from calcineurin inhibitors (CNI) to SRL may regress LVH in KT patients [6,7]. More recently, a randomized controlled study demonstrated that the use of everolimus (EVL) plus a reduced exposure of cyclosporine (CsA) proved effective in regressing LVH in KT recipients [8]. However, none of these studies included patients who had received renin-angiotensin system (RAS) blockers together with the m-TOR inhibitors during the first post-conversion year.…”
Section: Introductionmentioning
confidence: 99%